Presenilin-1 intron 8 polymorphism is not associated with autopsy-confirmed late-onset Alzheimer's disease. - Tysoe, C; Whittaker, J; Cairns, N; Atkinson, P; Harrington, C; Xuereb, J; Wilcock, G; Rubinsztein, D (1997)
Mutations in the presenilin-1 (PS-1) gene may account for the majority of familial early-onset Alzheimer's disease (EOAD) cases. However, there is controversy as to whether the bi-allelic intron 8 PS-1 polymorphism plays a role in late-onset AD (LOAD). As previous association studies with this polymorphism have all investigated clinically diagnosed LOAD cases, we have analysed the frequency of the PS-1 intronic polymorphism in a series of autopsy-confirmed early- (n = 54) and late-onset (n = 199) cases and a large control population of non-demented, aged individuals (n = 215). Our sample size should have had the power to reveal effects of the size previously reported for the PS-1 polymorphism, but we detected no significant increase in the 1/1 risk genotype distribution in EOAD or LOAD cases. Thus, we have been unable to find an association between the PS-1 intronic polymorphism and early- or late-onset AD within this autopsy-confirmed population.